Strategi Pengembangan Koleksi Reyog Corner Perpustakaan Universitas Muhammadiyah Ponorogo - Priatna, Yolan; Pratiwi, Amanda Candra (Daluang: Journal of Library and Information Science, 2021)
Introduction: Library collection development is a routine activity and must be carried out by all libraries. Even though it has become a routine activity, it is not uncommon for this activity to become difficult to do, as was the case with the Muhammadiyah University of Ponorogo Library which experienced difficulties in developing the Reyog Corner collection, a corner or reading corner containing various collections containing about Reyog and Ponorogo Regency. This study aims to determine the strategy carried out by the Muhammadiyah University of Ponorogo Library in developing a collection for that corner.Methodology: This study uses a qualitative method with a descriptive approach in conducting research.Results and Discussion: Based on data analysis and studies conducted, the authors found the results if the obstacles faced in developing collections for Reyog Corner were the lack of library materials containing the study/theme. However, various efforts were made to develop Reyog Corner, including establishing contacts with local governments, direct searches for authors, and independent searches based on subjects through various online shops.Conclusion: The results of this study are expected to be a reference for readers in developing collections in workplace libraries and private libraries, especially collections that have a certain uniqueness.